2014
DOI: 10.3390/en7085201
|View full text |Cite
|
Sign up to set email alerts
|

Dialectic Form Finding of Passive and Adaptive Shading Enclosures

Abstract: Form finding describes the process of finding a stable equilibrium shape for a system under a specific set of loads, for a set of boundary conditions and starting from an arbitrary initial geometry. However, form finding does not traditionally involve performance constraints such as energy-related criteria. Dialectic form finding is an extension of the process integrating energy-related design aspects. In this paper, dialectic form finding is employed as an approach for designing high performance architectural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…Kim et al [3] proposed an experimental configuration of an external shading device that would result in the most efficient cooling outcomes through adjustments to the slat angle. Passive and adaptive shading device designs can be found in [4]. Yener [5] developed a mathematical model to determine the optimal solution for fixed shading devices.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al [3] proposed an experimental configuration of an external shading device that would result in the most efficient cooling outcomes through adjustments to the slat angle. Passive and adaptive shading device designs can be found in [4]. Yener [5] developed a mathematical model to determine the optimal solution for fixed shading devices.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, numerical form-finding methods are combined with shape and structural behavioral constraints to develop adaptive structures that integrate active elements within their structural system. This approach is referred to as dialectic form finding (Adriaenssens et al, 2014b) and is illustrated in Fig. 1.…”
Section: Dialectic Form Findingmentioning
confidence: 99%
“…Numerical form-finding methods include methods such as the force density (Schek, 1974), thrust network analysis (Block, 2009), dynamic relaxation (Barnes, 1999) and non-linear Finite Element (FE) approaches (Pagitz and Mirats Tur, 2009). Extensive reviews of form-finding methods can be found in (Tibert and Pellegrino, 2003;Veenendaal and Block, 2012;Adriaenssens et al, 2014b). In this study, numerical form-finding methods are combined with shape and structural behavioral constraints to develop adaptive structures that integrate active elements within their structural system.…”
Section: Dialectic Form Findingmentioning
confidence: 99%
“…Because the total energy consumption in buildings accounts for nearly 40% of the primary energy use in many countries, a number of studies on energy-saving technologies for buildings have been conducted with a focus on the thermal performance of envelopes, efficiency enhancement of lighting and air-conditioning facilities, and renewable energy applications [4][5][6][7]. In order to reduce the lighting energy in buildings, high-efficiency light-emitting diode (LED) lamps and light-dimming control using daylight harvesting have been developed [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%